Central European Functional Programming School 5th Summer School, CEFP 2013, Cluj-Napoca, Romania, July 8-20, 2013, Revised Selected Papers - Zsók, Viktória; Horváth, Zoltán; Csató, Lehel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume presents the revised lecture notes of selected talks given at the Fifth Central European Functional Programming School, CEFP 2013, held in July 2013 in Cluj-Napoca, Romania. The 14 revised full papers presented were carefully reviewed and selected. The lectures cover a wide range of distributed and multicore functional programming subjects. The last 5 papers are selected papers of the PhD Workshop organized for the participants of the summer school.
Functional Programming for Domain-Specific Languages -- DSL in C++ Template Metaprogram -- The Idris Programming Language -- An Introduction to Task Oriented Programming -- Spreadsheet Engineering -- The EDSL's struggle for their sources -- Zipper-based Modular and Deforested Computations -- Tasklets: Client-side evaluation for iTask3.
Keywords: Computer programming; Software engineering; Programming languages (Electronic computers).; Computer logic; Programming Techniques; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs